COMMUNICATION AND ORGANIZATIONAL CHANGE IN THE DIGITAL TRANSFORMATION OF CORRESPONDENCE GOVERNANCE IN PT DIRGANTARA INDONESIA - Istiani, Ade Nur; Suherman, M. Tanziil; Adisatryo, Adisatryo (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2025)
This study explores the digital transformation of correspondence governance at PT Dirgantara Indonesia (PTDI) from a communication and organizational change perspective. The research aims to analyze how the digitization process of the company’s letter management system is implemented and to identify the challenges that arise during this transformation. Using Kurt Lewin’s Three Step Change Model as the analytical framework, the study examines how organizational communication influences employee readiness and adaptation to change. The research employs a qualitative instrumental case study approach, allowing for an in-depth understanding of the digitalization process within PTDI. Data were collected through interviews, observations, document analysis, and audiovisual materials. The findings reveal that the digital correspondence system improves efficiency and transparency in administrative processes. However, obstacles remain, particularly in the early stages of change, due to limited infrastructure and inconsistent employee engagement. The study concludes that effective communication and leadership support are critical to ensuring successful digital transformation and sustainable organizational change. Keywords: Communication, Correspondence Governance, Digital Transformation, Organizational Change, PT Dirgantara Indonesia